Larval morphology of Agnoshydrus Biström, Nilsson & Wewalka, 1997: description of A. thailandicus Okada, 2024 and phylogenetic comparison with other known Hyphydrini (Coleoptera: Adephaga, Dytiscidae) - Okada, Ryohei; Alarie, Yves; Michat, Mariano C. (Zootaxa, 2026)
The three larval instars of the Thailand endemic Agnoshydrus thailandicus Okada, 2024 are described for the first time, including a detailed chaetotaxy analysis of the cephalic capsule, head appendages, legs, last abdominal segment, and urogomphi. The phylogenetic position of Agnoshydrus Biström, Nilsson & Wewalka, 1997 is studied based on a cladistic analysis of 12 Hyphydrini species (nine genera) and 59 morphological larval characters. Although the phylogenetic relationships of Agnoshydrus within the tribe Hyphydrini remain unresolved, it seems reasonable to suggest a closer relationship with Desmopachria Babington, 1842, Hovahydrus Biström, 1982, and Microdytes J. Balfour-Browne, 1946.